A Study on the Comparison between the Chinese Structural Auxiliary Words “de” and the Relevant Word “dengan” in Indonesian Language - L.Cahyati, Leni; Liu, Haibo (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2025)
This research was to examine the Chinese structural auxiliary words “de” with the related Indonesian word “dengan”. The aims of this research were to disclose the correspondence between Chinese words “de” and relevant word “dengan” in Indonesian and also to elaborate their similarities and differences. The data of this research focused on the Chinese structural auxiliary words “de”, the Indonesian function word “dengan”. The writer analyzed the data by using comparative approach. The analysis would focus on the semantical, pragmatical and syntactical aspects. This research used descriptive qualitative method in analyzing data. The results of this research indicate that the Chinese structural auxiliary words “de” are correspond to the Indonesian function word “dengan” ,but the Chinese structural auxiliary words “de” can not be completely translated into “dengan” and the Indonesian function word “dengan” can not be completely translated into “de”.